Long Term Effects of Different Agro-forestry Systems on Soil Physical Health under Hilly Ecosystem of Meghalaya - Saha, R.; Mishra, V.K.; Tomar, J.M.S.; Kumar, Patiram (Indian Journal of Agroforestry, 2020)
Different agro-forestry systems (AFS) viz. Arboretum, Khasi mandarin, Assam lemon, Multistoried AFS (Alder + Tea + Black pepper), Silvi-horti-pastoral (Alder + Pineapple + Fodder) and Natural forest were evaluated to study the long-term effects on soil physical properties. These systems were developed in sloppy condition (30-50 % slope) at ICAR Research Complex for NEH Region, Umiam during 1987 - 1988. The soils were mostly clay to silty clay- in texture and acidic in reaction. After 15 years, soil bulk density of the various systems varied from 0.91 to 1.24 Mg m-3. Macro and micro aggregate percentage and mean weight diameter (MWD) were recorded in the order of natural forest> multistoried AFS > silvi-horti-pastoral > arboretum> Khasi mandarin> Assam lemon. The volume of residual pores (<0.5mm) was maximum in natural forest (57.93 %) followed by multistoried AFS (52.87 %), indicating it’s higher capacity to retain soil moisture. There is a sharp increase in dispersion ratio values in arboretum, Khasi mandarin and Assam lemon systems over the other AFS. The low apparent hydraulic conductivities under Khasi mandarin, arboretum and Assam lemon systems (0.38, 0.50, 0.53 ms-1 X 10-4, respectively) in comparison to natural forest, could be ascribed to high degree of soil dispersion. Soil moisture characteristics showed that at saturation stage, the water content was highest (62.18 %) in natural forest and lowest (52.91 %) in Khasi mandarin system. On the basis of investigated parameters, multistoried and silvi-horti-pastoral AFS appeared to be suitable for sustainable soil and crop productivity and resource conservation in hilly agro-ecosystems of Meghalaya.